2020
DOI: 10.1007/s00221-020-05745-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of acceleration and jerk in perception of above-threshold surge motion

Abstract: Inertial motions may be defined in terms of acceleration and jerk, the time-derivative of acceleration. We investigated the relative contributions of these characteristics to the perceived intensity of motions. Participants were seated on a high-fidelity motion platform, and presented with 25 above-threshold 1 s forward (surge) motions that had acceleration values ranging between 0.5 and 2.5 m/s 2 and jerks between 20 and 60 m/s 3 , in five steps each. Participants performed two tasks: a magnitude estimation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Similar to [ 39 ], who used two separate tasks to determine the relative contributions of accelerations and jerk to the perceived intensity of motions, we used (1) a Magnitude Estimation (ME) task to assess accuracy of perception, and (2) a 2-Interval Forced Choice (2IFC) task to assess precision of perception. Both tasks were used in each part of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to [ 39 ], who used two separate tasks to determine the relative contributions of accelerations and jerk to the perceived intensity of motions, we used (1) a Magnitude Estimation (ME) task to assess accuracy of perception, and (2) a 2-Interval Forced Choice (2IFC) task to assess precision of perception. Both tasks were used in each part of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Jerk (m/s 3 ) Average jerk is the time derivative of acceleration [44]. For each axis, a set amount of raw acceleration in a time (0.1, 0.5, 1.0) was summed, and the difference between each interval was calculated to generate the jerk value.…”
Section: Path Integrationmentioning
confidence: 99%
“…For these reasons, studies on multisensory and dynamic aspects of acceleration perception have solely been conducted with driving simulator setups. One example of this is a study in which participants had to rate the intensity of different motion profiles varying in velocity, acceleration, and jerk on a hexapod motion simulator 26 -here they found that this intensity is largely determined by acceleration cues. Similarly, in 16 longitudinal acceleration profiles were run on a hexapod simulator for absolute thresholds, yielding thresholds (JND) for acceleration of 4.25% and for jerk of 13.89% for one comparison baseline.…”
Section: Related Workmentioning
confidence: 99%